Blood Loss after Total Knee Arthroplasty and Autologous Transfusion - Miura, Hiromasa; Saikawa, Isao; Ogata, Kousuke; Tokunaga, Masami; Sugioka, Yoichi; Kawamura, Hideya (Orthopedics & Traumatology, 1994)
We retrospectively studied blood loss in 75 cases of total knee arthroplasty for osteoarthritis. Subjects were divided into two groups; Group A, tourniquet was released intraoperatively and hemostasis achieved with electrocoagulation. Group B; tourniquet remained inflated throughout the operative procedure and was released after a compressive dressing. The amount of intraoperative blood loss and total blood loss in group A were significantly larger than those in group B. We performed autologous transfusion with administration of recombinant erythropoietin to patients treated with total knee arthroplasty since 1990. Before performing this procedure, 42.9% of our patients required transfusion with homologous blood. We can avoid homologous transfusion in 94.7% of our patients by using autologous transfusion.